Remarkable consistency of spinal cord microvasculature in highly adapted diving odontocetes - Miller, Megan L.; Glandon, Hillary L.; Tift, Michael S.; Pabst, D. Ann; Koopman, Heather N. (Frontiers in Physiology, 2022)
Odontocetes are breath-hold divers with a suite of physiological, anatomical, and behavioral adaptations that are highly derived and vastly different from those of their terrestrial counterparts. Because of these adaptations for diving, odontocetes were originally thought to be exempt from the harms of nitrogen gas embolism while diving. However, recent studies have shown that these mammals may alter their dive behavior in response to anthropogenic sound, leading to the potential for nitrogen supersaturation and bubble formation which may cause decompression sickness in the central nervous system (CNS). We examined the degree of interface between blood, gases, and neural tissues in the spinal cord by quantifying its microvascular characteristics in five species of odontocetes (Tursiops truncatus, Delphinus delphis, Grampus griseus, Kogia breviceps, and Mesoplodon europaeus) and a model terrestrial species (the pig-Sus scrofa domesticus) for comparison. This approach allowed us to compare microvascular characteristics (microvascular density, branching, and diameter) at several positions (cervical, thoracic, and lumbar) along the spinal cord from odontocetes that are known to be either deep or shallow divers. We found no significant differences (p<0.05 for all comparisons) in microvessel density (9.30 to 11.18%), microvessel branching (1.60 to 2.12 branches/vessel), or microvessel diameter (11.83 to 16.079 µm) between odontocetes and the pig, or between deep and shallow diving odontocete species. This similarity of spinal cord microvasculature anatomy in several species of odontocetes as compared to terrestrial mammal is in contrast to the wide array of remarkable physio-anatomical adaptations marine mammals have evolved within their circulatory system to cope with the physiological demands of diving. These results, and other studies on CNS lipids, indicate that the spinal cords of odontocetes do not have specialized features that might serve to protect them from Type II DCS.